Dimensi Persepsi Juru Parkir Terhadap Efektivitas Uji Coba Parkir Elektronik di Tepi Jalan Umum Sebagai Upaya Peningkatan Pendapatan Asli Daerah Kabupaten Ponorogo - Setiawan, Salma Refia Rahayu; Purnomo, Rochmat Aldy; Cahyono, Yeni; Santoso, Slamet; Abas, Sayid (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Electronic Parking (E-Parking) is an innovation of parking services to realize safe, convenient, and transparent parking. The implementation of E-Parking aims to reduce the leakage of parking fees and illegal parking attendants so that it can increase the Regional Original Revenue (PAD) of Ponorogo Regency. This study analyzes the perceptions of parking attendants regarding the effectiveness of the E-parking trial on public roadsides on increasing PAD. Primary data collected through interviews, observations, and documentation were used in the descriptive qualitative methodology of this research. The informants in this study are parking attendants who are on duty at the points used as E-Parking trial points. The effectiveness of the E-parking trial based on the perceptions of parking attendants was ineffective because there were still parking attendants who were reluctant to operate the parking equipment because parking attendants felt that E-parking made the work inefficient and slowed down the work because the parking equipmen was always constrained. The effectiveness of the E-parking trial as an effort to increase PAD has been effective, this can be assessed from the increase in PAD from parking fees doubled when the trial was implemented compared to before the trial was carried out. Keywords: Regional Original Income, Parking Attendant, Regional Levy, Public Roadside Parking, Ponorogo